Le particolarità dell'indagine previa nel processo penale canonico - Szablocs Szuromi, Anzelm ("Iustitia et iudicium" ; 4, 2010)
The basic purpose of the preliminary investigation is the discovery of the relevant facts of the case, circumstances and imputability of the person by reasion. Based on this observation, the ordinary is the one who can decide whether the commission of the delict is really presumptiove; whether he can and will initiate a process to inflict a penalty and whether a judicial of administrative penal process must be used